Sobrepeso pregestacional como factor de riesgo para desarrollar diabetes mellitus gestacional en mujeres atendidas en el Hospital Regional Docente de Trujillo, 2011 – 2016 - Ibáñez Miñano, César Iván (2019)
Introduction: Gestational diabetes is a disorder of variable frequency in pregnancy, which leads to maternal-infant risk of variable morbidity and mortality, including maternal and infant death, pre-pregnancy overweight has been related to this event. Objective: To establish if pre-pregnancy overweight is a risk factor for the development of gestational diabetes mellitus in women treated at the Hospital Regional Docente de Trujillo (HRDT), 2011-2016. Method: Case-control study in which 270 medical records (135 cases with gestational diabetes and 135 controls) of pregnant women attended in the gynecological-obstetric service of the HRDT between 2011 and 2016 were reviewed. Odds Ratio (OR) was calculated for establish their association and Pearson's Chi-square test for statistical significance. Results: Pre-pregnancy overweight occurred in 74% of all pregnant women, and in 84% of those with gestational diabetes, representing a risk factor for this disease (OR: 2.99, p <0.001). Conclusion: pre-pregnancy overweight is a risk factor for the development of gestational diabetes mellitus in women treated in the HRDT, 2011-2016.